Aberrant developmental titin splicing and dysregulated sarcomere length in Thymosin β4 knockout mice. (January 2017) - Smart, Nicola; Riegler, Johannes; Turtle, Cameron W.; Lygate, Craig A.; McAndrew, Debra J.; Gehmlich, Katja; Dubé, Karina N.; Price, Anthony N.; Muthurangu, Vivek; Taylor, Andrew M.; Lythgoe, Mark F.; Redwood, Charles; et al.
Abstract: Sarcomere assembly is a highly orchestrated and dynamic process which adapts, during perinatal development, to accommodate growth of the heart. Sarcomeric components, including titin, undergo an isoform transition to adjust ventricular filling. Many sarcomeric genes have been implicated in congenital cardiomyopathies, such that understanding developmental sarcomere transitions will inform the aetiology and treatment. We sought to determine whether Thymosin β4 (Tβ4), a peptide that regulates the availability of actin monomers for polymerization in non-muscle cells, plays a role in sarcomere assembly during cardiac morphogenesis and influences adult cardiac function. In Tβ4 null mice, immunofluorescence-based sarcomere analyses revealed shortened thin filament, sarcomere and titin spring length in cardiomyocytes, associated with precocious up-regulation of the short titin isoforms during the postnatal splicing transition. By magnetic resonance imaging, this manifested as diminished stroke volume and limited contractile reserve in adult mice. Extrapolating to an in vitro cardiomyocyte model, the altered postnatal splicing was corrected with addition of synthetic Tβ4, whereby normal sarcomere length was restored. Our data suggest that Tβ4 is required for setting correct sarcomere length and for appropriate splicing of titin, not only in the heart but also in skeletal muscle. Distinguishing between thin filament extension and titin splicing as the primary defect is challenging, as these events are intimately linked. The regulation of titin splicing is a previously unrecognised role of Tβ4 and gives preliminary insight into a mechanism by which titin isoforms may be manipulated to correct cardiac dysfunction. Highlights: Thymosin β4 (Tβ4) regulates sarcomere length in the postnatal heart. Τβ4 KO mice have shorter thin filaments and express shorter titin isoforms. Τβ4 KO mice possess limited contractile reserve, in response to dobutamine stress. Splicing may be a novel role for Tβ4 and a target to correct cardiac dysfunction.